The King Vision™ video laryngoscope for awake intubation: series of cases and literature review - Gaszynska E; Gaszynski T (Dove Medical Press, 2014)
Ewelina Gaszynska, Tomasz GaszynskiDepartment of Emergency Medicine and Disaster Medicine, Medical University of Lodz, Lodz, PolandAbstract: Intubation of patients with a supraglottic mass causing obstruction of the glottis remains a difficult problem for the experienced anesthesiologist. Awake fiberscopic endotracheal intubation is the recommended approach in such cases; however, use of a video laryngoscope for awake intubation can be an alternative to a fiberscope. Here we present two cases of awake intubation using a King Vision™ video laryngoscope in patients with a supraglottic mass, and a literature review on use of video laryngoscopes for awake intubation. After topical anesthesia and sedation with opioids, the patients were successfully intubated.Keywords: airway management, difficult airway, awake intubation, video laryngoscope